Merokok Sebagai Faktor Risiko Thyroid Eye Disease - Febri Nadyanti; M. Yusran (Majority, 2021)
Thyroid-Associated Ophthalmopathy (TAO), known as Graves Ophthalmopathy (GO) or Thyroid Eye Disease (TED), is the most common cause of orbital disease in adults and a significant cause of morbidity in patients with Graves' disease. The main cause of this disease is the occurence of inflammation, which results in the overproduction of glycosaminglycans (GAG) and adipogenesis. This process is caused by the release of local inflammatory cytokines. Smoking is suspected to be one of risk factor that associated with the severity of TED. Tobacco smoke has cyanide, this substance will be converted into chemical thyocyanates when inhaled. Exposure to that smoke can increase the production and adipogenesis which is the cause of Thyroid Eye Disease.